Open release of male mosquitoes infected with a wolbachia biopesticide: field performance and infection containment. - Linda O'Connor; Catherine Plichart; Ayo Cheong Sang; Corey L Brelsfoard; Hervé C Bossin; Stephen L Dobson (PLoS Neglected Tropical Diseases, 2012)
Background Lymphatic filariasis (LF) is a globally significant disease, with 1.3 billion persons in 83 countries at risk. A coordinated effort of administering annual macrofilaricidal prophylactics to the entire at-risk population has succeeded in impacting and eliminating LF transmission in multiple regions. However, some areas in the South Pacific are predicted to persist as transmission sites, due in part to the biology of the mosquito vector, which has led to a call for additional tools to augment drug treatments. Autocidal strategies against mosquitoes are resurging in the effort against invasive mosquitoes and vector borne disease, with examples that include field trials of genetically modified mosquitoes and Wolbachia population replacement. However, critical questions must be addressed in anticipation of full field trials, including assessments of field competitiveness of transfected males and the risk of unintended population replacement. Methodology/principal findings We report the outcome of field experiments testing a strategy that employs Wolbachia as a biopesticide. The strategy is based upon Wolbachia-induced conditional sterility, known as cytoplasmic incompatibility, and the repeated release of incompatible males to suppress a population. A criticism of the Wolbachia biopesticide approach is that unintended female release or horizontal Wolbachia transmission can result in population replacement instead of suppression. We present the outcome of laboratory and field experiments assessing the competitiveness of transfected males and their ability to transmit Wolbachia via horizontal transmission. Conclusions/significance The results demonstrate that Wolbachia-transfected Aedes polynesiensis males are competitive under field conditions during a thirty-week open release period, as indicated by mark, release, recapture and brood-hatch failure among females at the release site. Experiments demonstrate the males to be 'dead end hosts' for Wolbachia and that methods were adequate to prevent population replacement at the field site. The findings encourage the continued development and extension of a Wolbachia autocidal approach to additional medically important mosquito species.